Occipital Seizures V. Migraine Aura - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Three children, ages 13 to 17 years, with occipital seizures resembling the visual aura of migraine are reported from St Thomas' Hospital, London, England.